Intranasal administration of recombinant Netrin-1 attenuates neuronal apoptosis by activating DCC/APPL-1/AKT signaling pathway after subarachnoid hemorrhage in rats. (June 2017) - Xie, Zongyi; Huang, Lei; Enkhjargal, Budbazar; Reis, Cesar; Wan, Weifeng; Tang, Jiping; Cheng, Yuan; Zhang, John H.
Abstract: Neuronal apoptosis is a crucial pathological process in early brain injury after subarachnoid hemorrhage (SAH). The effective therapeutic strategies to ameliorate neuronal apoptosis are still absent. We intended to determine whether intranasal administration of exogenous Netrin-1 (NTN-1) could attenuate neuronal apoptosis after experimental SAH, specifically via activating DCC-dependent APPL-1/AKT signaling cascade. Two hundred twenty-five male Sprague-Dawley rats were subjected to the endovascular perforation model of SAH. Recombinant human NTN-1 (rNTN-1) was administered intranasally. NTN-1 small interfering RNA (siRNA), APPL-1 siRNA, and AKT inhibitor MK2206 were administered through intracerebroventricular (i.c.v.) injection. SAH grade, neurological score, neuronal apoptosis assessed by cleaved caspase-3 (CC-3) expression and Fluoro-Jade C (FJC) staining, double immunofluorescence staining, and Western blot were examined. Our results revealed that endogenous NTN-1 level was increased after SAH. Administration of rNTN-1 improved neurological outcomes at 24 h and 72 h after SAH, while knockdown of endogenous NTN-1 worsened neurological impairments. Furthermore, exogenous rNTN-1 treatment promoted APPL-1 activation, increased phosphorylated-AKT and Bcl-2 expression, as well as decreased apoptotic marker CC-3 expression and the number of FJC-positive neurons, thereby alleviated neuronal apoptosis. Conversely, APPL-1 siRNA and MK2206 abolished the anti-apoptotic effect of exogenous rNTN-1 at 24 h after SAH. Collectively, intranasal administration of exogenous rNTN-1 attenuated neuronal apoptosis and improved neurological function in SAH rats, at least in apart via activating DCC/APPL-1/AKT signaling pathway. Highlights: Subarachnoid hemorrhage (SAH) resulted in neuronal apoptosis and neurological deficits in a rat model. Intranasal administration of exogenous NTN-1 significantly attenuated neuronal apoptosis and improved neurological functions. The mechanisms of rNTN-1-mediated anti-apoptosis may be mediated by activating DCC-dependent APPL-1. The downstream signaling of NTN-1/DCC/APPL-1 in subarachnoid hemorrhage may be related to AKT, Bcl-2 and Caspase-3. rNTN-1 may be an attractive candidate for anti-apoptosis treatment in early brain injury after SAH.